2013
DOI: 10.1242/dev.091124
|View full text |Cite
|
Sign up to set email alerts
|

C. elegansGATA factors EGL-18 and ELT-6 function downstream of Wnt signaling to maintain the progenitor fate during larval asymmetric divisions of the seam cells

Abstract: SUMMARYThe C. elegans seam cells are lateral epithelial cells arrayed in a single line from anterior to posterior that divide in an asymmetric, stem cell-like manner during larval development. These asymmetric divisions are regulated by Wnt signaling; in most divisions, the posterior daughter in which the Wnt pathway is activated maintains the progenitor seam fate, while the anterior daughter in which the Wnt pathway is not activated adopts a differentiated hypodermal fate. Using mRNA tagging and microarray an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
79
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 63 publications
0
79
0
Order By: Relevance
“…These visually accessible cells repeatedly divide asymmetrically in a stem-cell-like pattern during larval development, and cell fate determination for each of these divisions is dependent on the WbA pathway (supplementary material Fig. S1; Mizumoto and Sawa, 2007;Kanamori et al, 2008;Huang et al, 2009;Banerjee et al, 2010;Gleason and Eisenmann, 2010;Ren and Zhang, 2010;Harterink et al, 2011;Yamamoto et al, 2011;Gorrepati et al, 2013;Hughes et al, 2013). Thus, the lineage maintains a constant number of seam cells (posterior WbA-signaled daughters) while increasing the number of hypodermal nuclei (anterior Wnt-independent daughters).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These visually accessible cells repeatedly divide asymmetrically in a stem-cell-like pattern during larval development, and cell fate determination for each of these divisions is dependent on the WbA pathway (supplementary material Fig. S1; Mizumoto and Sawa, 2007;Kanamori et al, 2008;Huang et al, 2009;Banerjee et al, 2010;Gleason and Eisenmann, 2010;Ren and Zhang, 2010;Harterink et al, 2011;Yamamoto et al, 2011;Gorrepati et al, 2013;Hughes et al, 2013). Thus, the lineage maintains a constant number of seam cells (posterior WbA-signaled daughters) while increasing the number of hypodermal nuclei (anterior Wnt-independent daughters).…”
Section: Introductionmentioning
confidence: 99%
“…Activation or repression of WbA results in increased or decreased seam cell numbers, respectively. At least one direct target of SYS-1 and POP-1, EGL-18, is also differentially expressed in the seam daughters; EGL-18 expression is elevated in the posterior cell with a high SYS-1:POP-1 ratio and is reduced or absent in the anterior daughter with a low SYS-1:POP-1 ratio (Gorrepati et al, 2013). Other recent studies have analyzed the genetics of Wnt signaling components in C. elegans and the effects these components have on seam cell number, providing several potential regulators of SYS-1 asymmetry (Huang et al, 2009;Banerjee et al, 2010;Gleason and Eisenmann, 2010;Ren and Zhang, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While we have mainly studied components of the inhibitory side of the genetic network, it is still unclear what transcription factor(s) are primarily responsible for the activation of eff-1. Most mutations that alter the frequency of the P3.p hyp7/fusion cell fate lie in proteins that act as inhibitors to the cell fusion process, such as most Wnt pathway components, ceh-20, ref-1, ref-2, egl-18/elt-5, dyamin-1,andrab-5 (Alper andKenyon, 2001, 2002;Gorrepati et al, 2013;Koh et al, 2002;Smurova and Podbilewicz, 2016). Fewer have been found that are required for eff-1 activation, which could also provide additional noise or variability into the cell fate decision.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a lin-22 loss-of-function mutation decreases P3.p cell fusion frequencies (Katsanos et al, 2017;Schlager et al, 2006). LIN-22 codes for a Hairy/Enhancer of Split-related transcription factor, which was found to act in the Wnt pathway by repressing egl-18, a GATA transcription factor, also a repressor of cell fusion in the seam cells (Gorrepati et al, 2013;Katsanos et al, 2017;Wrischnik and Kenyon, 1997). Therefore, variations in not only the inhibitor molecules, but LIN-22 could create noise and variability that leads to stochastic eff-1 expression and cell fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Gorrepati et al (2013) reported that EGL-18 overexpression in a Wnt-sensitized background is capable of activating seam cell marker expression in head and ventral hypodermis and that EGL-18 is required for seam cell fate specification. It has also been previously reported that frk-1 acts upstream of elt-18 and elt-3 in regulating hypodermal cell specification during embryonic development (Putzke et al 2005).…”
Section: Discussionmentioning
confidence: 99%